Religião e criminalidade: da cultura da morte à cultura da paz e do perdão - Souza, Robson Sávio Reis (Horizonte, 2005)
One of the main current social problems is the appalling growth of various kinds of violent crime in many Brazilian cities. The current portrait of violence in Brazil can be thus designed: the growth of urban delinquency, with a remarkable increase in the number of murders connected to drug traffic in big cities; the consolidation of organised crime, through nets of international traffic, organs and human beings’ traffic, international smuggling and piracy mafias; an increase in the violation of human rights, jeopardising social and political order; and, in the rural area, the explosion of conflicts motivated by an agrarian structure of concentration and historical violence. How can religion, as an instrument of social cohesion, contribute to revert that hideous wave of criminality and violence? This is our scope.